The Role of Telehealth in Strengthening Health Education and Health Service Quality: A Systematic Review - Mawar Hatem Al-Obaidy; Zhian Abdulah (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aims to systematically examine the role of telehealth in strengthening health education while simultaneously improving the quality of healthcare services, particularly in contexts with limited access to face-to-face healthcare delivery. Methodology: This study employed a systematic review method. Data were collected from PubMed, Scopus, ScienceDirect, and ProQuest databases using a PEO-based search strategy. Article screening followed PRISMA guidelines, and methodological quality was assessed using the Critical Appraisal Skills Programme checklist. Descriptive and thematic synthesis techniques were applied. Main Findings: The findings indicate that telehealth enhances healthcare accessibility, service efficiency, continuity of care, and patient engagement. Telehealth platforms such as video conferencing and audio-based communication support both clinical services and health education, enabling improved patient understanding, self-management, and satisfaction across diverse healthcare settings. Novelty/Originality of this study: This study offers a novel contribution by synthesizing evidence on telehealth as an integrated approach combining healthcare service delivery and structured health education. Unlike previous fragmented studies, this review highlights the dual function of telehealth in improving service quality and patient empowerment within digital health systems.